2018
DOI: 10.3906/zoo-1708-37
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the cannibalistic behavior of ladybird beetle Coccinella septempunctata L. (Coleoptera: Coccinellidae) under laboratory conditions

Abstract: Cannibalism or intraspecific predation, where one species feeds on individuals of its own species, is a widespread phenomenon in most aphidophagous coccinellids. Laboratory studies were conducted on the cannibalistic behavior of various developmental stages of Coccinella septempunctata L. (Coleoptera: Coccinellidae) in the presence and absence of natural food, Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae). In both the presence and absence of aphids, the eggs and 1st and 2nd instars of C. septempunctata w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[27] reported that in the case of Harmonia axyridis, production of eggs is considered an impact factor for the target of cannibalism and give the missing feeder in their food and therefore eggs were more important than instar stages for cannibalism, which when eat is scarcity [28,29] . However, many researcher [30,9] , these proved that most insects are reluctant of self-predation. All stages of observed different stages of eggs cannibalism as well as the fourth larval instars of coccinellid seemed the increased consumed compering other instars, whether feeding eggs cannibalism [31,32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] reported that in the case of Harmonia axyridis, production of eggs is considered an impact factor for the target of cannibalism and give the missing feeder in their food and therefore eggs were more important than instar stages for cannibalism, which when eat is scarcity [28,29] . However, many researcher [30,9] , these proved that most insects are reluctant of self-predation. All stages of observed different stages of eggs cannibalism as well as the fourth larval instars of coccinellid seemed the increased consumed compering other instars, whether feeding eggs cannibalism [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…In case of absence or presence of prey, C. septempunctata behaved as a conspecific predator. Many studies showed that scarcity of prey was the absolute reason of cannibalism in C. septempunctata [9] . The scarcity of prey may not be the important reason for cannibalism in C. septempunctata [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The primary factor influencing cannibalism and its level of satiation is food deprivation (Dixon 2000) [6] . If the natural food is readily available, the incidences of cannibalism decline suggesting that cannibalism among larvae is inversely correlated with food supply (Khan and Yoldas 2018) [16] . Starved fourth instar larvae disregarded the toxicity of non-conspecific eggs due to their size and voracity.…”
Section: Discussionmentioning
confidence: 99%
“…(1999) in a study on H. axyridis have reported that third instars avoided cannibalism of related victims and took longer and showed higher encounter rates to cannibalise related victims than unrelated victims. The highest percentage of eggs cannibalised by fourth instars may be attributed to increased evolutionary survival pressure and higher energetic needs required for pupation (Khan et al ., 2003; Jafari, 2012; Khan and Yoldas, 2018a, b). The results suggest that possibly the nutritional requirements of larval instars vary based on the developmental stage which in turn regulates predatory prey consumption.…”
Section: Discussionmentioning
confidence: 99%